Size fractionation of bioaerosol emissions from green waste composting - Ferguson, Robert M. W.; Neath, Charlotte E. E.; Nasir, Zaheer A.; Garcia Alcega, Sonia; Tyrrel, Sean F.; Coulon, Frederic; Dumbrell, Alex J.; Colbeck, Ian; Whitby, Corinne (Elsevier, 2020)
Particle size is a significant factor in determining the dispersal and inhalation risk from bioaerosols. Green-waste composting is a significant source of bioaerosols (including pathogens), but little is known about the distribution of specific taxa across size fractions. To characterise size fractionated bioaerosol emissions from a compost facility, we used a Spectral Intensity Bioaerosol Sensor (SIBS) to quantify total bioaerosols and qPCR and metabarcoding to quantify microbial bioaerosols. Overall, sub-micron bioaerosols predominated, but molecular analysis showed that most (>75%) of the airborne microorganisms were associated with the larger size fractions (>3.3 µm da). The microbial taxa varied significantly by size, with Bacilli dominating the larger, and Actinobacteria the smaller, size fractions. The human pathogen Aspergillus fumigatus dominated the intermediate size fractions (>50% da 1.1–4.7 µm), indicating that it has the potential to disperse widely and once inhaled may penetrate deep into the respiratory system. The abundance of Actinobacteria (>60% at da < 2.1 µm) and other sub-micron bioaerosols suggest that the main health effects from composting bioaerosols may come from allergenic respiratory sensitisation rather than directly via infection. These results emphasise the need to better understand the size distributions of bioaerosols across all taxa in order to model their dispersal and to inform risk assessments of human health related to composting facilities
Keywords: Aspergillosis; Actinobacteria; Aspergillus fumigatus; Spectral Intensity Bioaerosol Sensor (SIBS); Human health Pathogens; Bioaerosols Composting